2017
DOI: 10.1007/s13300-017-0258-3
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training for Glycemic Control, Muscular Strength, and Lean Body Mass in Old Type 2 Diabetic Patients: A Meta-Analysis

Abstract: IntroductionType 2 diabetes (T2D) in elderly patients is associated with accelerated loss of skeletal muscle mass and strength. However, there are few meta-analysis reviews which investigate the effects of resistance training (RT) on glycemic control and skeletal muscle in the patients.MethodsThree electronic databases were searched (from the earliest date available to November 2016). Studies were included according to the inclusion criteria: T2D patients at least 60 years old, fasting plasma glucose of at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
55
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 75 publications
10
55
0
5
Order By: Relevance
“…Overall, CRF improved with HT, and muscle strength increased with both HT and MERT. Similarly to previous meta‐analytic research, general RT improved these physical fitness components. As it might be assumed, AT led to superior improvement of CRF than HT and general RT, and HT, MERT and general RT showed more pronounced increases in muscle strength than AT.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Overall, CRF improved with HT, and muscle strength increased with both HT and MERT. Similarly to previous meta‐analytic research, general RT improved these physical fitness components. As it might be assumed, AT led to superior improvement of CRF than HT and general RT, and HT, MERT and general RT showed more pronounced increases in muscle strength than AT.…”
Section: Discussionmentioning
confidence: 54%
“…Previous meta‐analyses have observed that RT characteristics did not (or scarcely) explain individually the between‐study heterogeneity in the magnitude of HbA1c, whereas the characteristics of patients with T2DM explained it slightly more. However, evidence about factors explaining between‐study variance on these clinical outcomes is almost inexistent.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Sarcopenia, age‐related losses in the quantity of skeletal muscle mass as well as diminished muscle strength and/or physical performance, is associated with multiple adverse health consequences, including an increased risk of falls, fractures, and frailty, which can lead to a loss of independence and disability, increased morbidity and mortality, and reduced quality of life . In recent years, increasing attention has been paid to resistance training as a useful adjunctive tool for increasing muscle mass and strength . Resistance training programs in previous studies, however, required expensive exercise machines and supervised instruction .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In recent years, increasing attention has been paid to resistance training as a useful adjunctive tool for increasing muscle mass and strength. [4][5][6] Resistance training programs in previous studies, however, required expensive exercise machines and supervised instruction. [5][6][7] For some elderly people, access to exercise facilities is limited and compliance may be poor.…”
Section: Introductionmentioning
confidence: 99%